Abnormal vibration perception threshold alters the gait features in type 2 diabetes mellitus patients - Dong, Lining; Hu, Yanyun; Xu, Lei; Zeng, Hui; Shen, Wenqi; Esser, Patrick; Dawes, Helen; Liu, Fang (Frontiers in Endocrinology, 2023)
Objective: It is still unclear how the abnormal foot sensation influences the gait during walking in type 2 diabetes mellitus (T2DM). For the purpose of gaining a better insight into the alterations of detailed gait parameters and figuring out the important aspect in the gait indexes by peripheral neuropathy in elder T2DM patients, we compared the gait features in participants with normal glucose tolerance (NGT) controls, as well as diabetic individuals complicated with and without peripheral neuropathy. Subjects and Methods: Gait parameters was observed during the 10-m walk on the flat land among different conditions of diabetes in 1741 participants from three clinical centers. Subjects were divided into 4 groups: persons with NGT were taken as control groups, patients with T2DM including 3 subgroups: DM control (no chronic complications), DM-DPN (DM complicated only with peripheral neuropathy), and DM-DPN+LEAD (DM complicated with both neuropathy and artery disease). The clinical characteristics and gait parameters were assessed and compared among these four groups. Analyses of variance were employed to verify possible differences of gait parameters between groups and conditions. Stepwise multivariate regression analysis was performed to reveal possible predictors of gait deficits. ROC curve analysis was employed to find any discriminatory power of DPN for the step time. Results: In participants burdened with DPN, whether complicated with LEAD or not, step time increased sharply (p<0.05). Stepwise multivariate regression models showed that independent variables of gait abnormality were sex, age, leg length, vibrating perception threshold (VPT), and ABI as well (p<0.01). While, VPT was listed as significant independent predictor of step time, SDA and SDB (p<0.05). ROC analysis was explored to find the discriminatory power of DPN for occurrence of increased step time. The AUC value was 0.608 (95% CI: 0.562-0.654, p < 0.01), and the cut-off point was 538.41ms accompanied by higher VPT. Conclusions: In addition to sex, age and leg length, VPT was a distinct factors that associated with altered gait parameters. Diabetic peripheral neuropathy is associated with increased step time and the step time increases with the worse VPT in type 2 diabetes.